The world of Thomas Jeremiah Charles Town on the eve of the American Revolution - Ryan, William Randolph, 1975- (Oxford University Press, 2010)
Profiling the port of Charles Town, South Carolina, during the two-year period leading up to the Declaration of Independence, this history focuses on the hanging and burning of Thomas Jeremiah, a free African American harbour pilot accused of plotting a slave insurrection in 1775.